Endovascular management of chronic post-dissection aneurysms - Oikonomou, Kyriakos; Katsargyris, Athanasios; Ritter, Wolfgang; Spinelli, Domenico; Seto, Yuki; Verhoeven, Eric L. (Annals of Cardiothoracic Surgery; Vol 3, No 3 (May 31, 2014): Type B Aortic Dissection (I), 2014)
Open repair is still the gold standard in acute type A dissection. Endovascular repair is advocated for complicated acute type B dissections. Recent evidence also supports the role of endovascular repair in a larger proportion of uncomplicated acute type B dissections. The role of endovascular repair in chronic post-dissection aneurysms, however, is still unclear. Most commonly, post-dissection aneurysms involve the thoracoabdominal aorta, making the use of fenestrated/branched stent-grafts to achieve complete aneurysm exclusion mandatory. These fenestrated/branched stent-grafts have been used with success in atherosclerotic thoracoabdominal aortic aneurysms (TAAAs). In chronic post-dissection aneurysms, however, additional technical challenges arise. The usually narrow true lumen makes the use of branches more tedious and overall planning difficult. A second technical challenge relates to the fact that visceral branches can also originate from the false lumen. In such cases, perforation of the stiff chronic dissection flap is required to obtain access to the vessel. During the period January 2010 to November 2013, 17 patients (13 males, mean age 65±7.8 years) with chronic thoracoabdominal aneurismal degeneration following acute dissection were treated in our department with the use of fenestrated/branched stentgrafts. Technical success was achieved in all cases (100%). Perioperative mortality was two (11.8%) patients. One patient died due to multiple organ failure and one due to cardiac failure. No case of paraplegia was observed. During a 12-month median follow-up (range, 4-28 months) no aneurysm-related deaths were observed. Reintervention was required in three cases to repair a type Ib endoleak from a side branch. Endovascular treatment with fenestrated/branched stent-grafts is feasible for chronic postdissection aneurysms. Standard thoracic stent-grafting is an option in a minority of patients, when the aneurysm is limited to the thoracic segment. Fenestrated and branched devices can successfully be used for aneurysms extending to the thoracoabdominal aorta.